Food availability and flight routes for migratory birds: a GIS approach - Tattoni, Clara; Soardi, Erica; Zatelli, Paolo; Ciolli, Marco (PeerJ Preprints, 2016)
Bird migration is a wide studied phenomenon but still many factors that influence migratory flows remain unknown or poorly understood. Food availability en route is particularly important for many species and can affect their migration success, pattern and timing but this relationship have not often been addressed at wide scale due to the lack of spatial models of food availability on the terrain.The aim of this work is to fill this gap with a GIS-database approach that links together spatial and non-spatial information in order to map and measure food availability in the different periods of the year in the SE Alps, an important node of European migratory routes. We created a unique database that contains information on the presence and periods of fruitification of 52 wild plants carriyng berries and a series of original cartographic themes. With this approach we were able to identify various flyways and compare them with known stopover sites, ringing stations and food availability using a mix of techniques of statistical geostatistical and interpretation of ecological data.
Keywords: wild berries; food availability; GRASS GIS; 3d visibility; forest types; QGIS; Open source; R-statistics; kernel; bird migration